Duodenal Adenocarcinoma Mimicking Metastasis of Prostate Cancer on 18F–Prostate-Specific Membrane Antigen–1007 PET/CT. (January 2021) - Soeda, Fumihiko; Watabe, Tadashi; Kato, Hiroki; Uemura, Motohide; Nonomura, Norio
Abstract : Abstract: A 76-year-old man with dyspnea (initial prostate-specific antigen [PSA]: 216 ng/mL) underwent 18 F-FDG PET/CT, with uptake in the prostate, lymph nodes, fifth thoracic vertebra (T5), and cricoid cartilage. A biopsy revealed prostate adenocarcinoma (Gleason score 4 + 5, cT4 N1 M1). On initiation of combined androgen blockade therapy, PSA value decreased. However, 4 years later, in a castration-resistant state (PSA 2.14 ng/mL), CT and bone scintigraphy revealed a duodenal tumor and T5 metastasis. 18 F–prostate-specific membrane antigen–1007 PET/CT showed uptake in the already known T5 metastasis (SUVmax, 33.55) and even in the duodenal tumor (16.55). The latter was histologically diagnosed as duodenal adenocarcinoma.